2017
DOI: 10.1002/ppap.201700123
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular responses to reactive oxygen and nitrogen species, and lipid peroxidation in apoptotic cells cultivated in plasma-activated medium

Abstract: A mechanism of the cytotoxicity of plasma-activated medium (PAM) is revealed by examining the intracellular effects of reactive oxygen nitrogen species (RONS) and lipid oxidation. PAM is cell culture medium activated by irradiation using non-equilibrium atmospheric-pressure plasma using pure Ar gas in ambient air. Extracellular RONS in PAM induced the apoptotic death of HeLa cells. Temporal changes in intracellular RONS, such as ONOO − , NO, and O À 2 , were analyzed. Intracellular RONS generation in HeLa cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 50 publications
3
18
0
Order By: Relevance
“…Figures (a, b) show the H 2 O 2 levels in the stored PAM. Figures (c, d) Figures 3 and 4, it can be stated that H 2 O 2 mainly contributes to the death of cancer cells after the indirect cold plasma irradiation on the culture medium, as previously suggested [31,32]. [23,37].…”
Section: Measurement Of Nitrite Concentration In Pam and Pamsupporting
confidence: 72%
See 1 more Smart Citation
“…Figures (a, b) show the H 2 O 2 levels in the stored PAM. Figures (c, d) Figures 3 and 4, it can be stated that H 2 O 2 mainly contributes to the death of cancer cells after the indirect cold plasma irradiation on the culture medium, as previously suggested [31,32]. [23,37].…”
Section: Measurement Of Nitrite Concentration In Pam and Pamsupporting
confidence: 72%
“…Additionally, cell death by ME-APPJ (788 MHz) utilizing a coaxial transmission line resonator (CTLR) was also confirmed [25]. As such, many studies on the mechanism by which CAP induces cancer cell death have been reported [26][27][28][29][30][31][32][33], but for the indirect treatment utilizing PAM, there is still a lack of research on physical changes in the stage before death occurs.…”
Section: Introductionmentioning
confidence: 94%
“…Plasmas are multi-component systems generating UV radiation, visible light, electromagnetic fields, thermal radiation, electrons and ions, and reactive oxygen species (ROS) and reactive nitrogen species (RNS) [2]. The latter play a crucial role in mediating the plasma effects in cells [3][4][5] by mediating oxidative modifications [6][7][8] to induce signaling pathways [9][10][11]. First discovered as a new tool for disinfection and wound healing [12][13][14], plasma also demonstrates cytotoxicity towards cancer cells [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The chemical components produced by CAPs, identified as the active agents responsible for the biological effects, have been extensively studied [ 6 , 7 ]. The reactive oxygen and nitrogen species (RONS) generated and delivered by plasma cause functional and structural damage to lipids in cell membranes [ 8 ], oxidize proteins [ 9 ], induce DNA breaks [ 10 ], and promote cell death by different mechanisms [ 11 , 12 ]. In contrast, the physical components produced by plasma such as UV photons and electromagnetic fields on their own have a negligible cellular impact [ 13 ].…”
Section: Introductionmentioning
confidence: 99%